Evaluasi Kualitas Website Pemerintah Daerah Dengan Menggunakan Webqual (Studi Kasus Pada Kabupaten Ogan Ilir) - Candra Irawan (Jurnal Sistem Informasi, 2012)
Quality evaluation of the local government is the basic concept of this paper. Webqual is one of website quality measurement methods based on user preceptions. According to the data analysis we have correlation koefisien number, R Square, is 0,998. This shows that three dimensionals Webqual are contributing 99,8% for the website quality level and the rest, 0,02%, is contributed by another factors. From the regresion equation shows that the independen variables from the usability dimension is giving significant influence to the website quality by coeficient 1,102, information quality dimension by 1,050 and interaction quality dimension by 1,041. According to questioner results, we would like to give recommendations such as changing website appearence become more attractive, adding more accurate, clear, detail, and up date informations so that people can get faster information from another local goverment.Index Term — Regresi, Website, Webqual